Factors that influence the usage of TM Net Streamyx provided by TM Net Sdn Bhd: Case study in Shah Alam / Nurnadia Zaini - Zaini, Nurnadia (Faculty of Business and Management, 2006)
The researcher has decided to focus on the "Factors that influence the usage of TM Net Streamyx provided by TM Net Sdn Bhd: Case Study in Shah Alam. The researcher is going to study further more on the usage of TM Net Streamyx whether they are the new user of TM Net Streamyx or they switch from the Dial-up Internet access to TM Net Streamyx. Apart from that, the researcher will know the frequency and the duration for each usage ofTM Net Streamyx whether they are the high intense user, moderate intense user, or low intense user of TM Net Streamyx. This study also focuses on the factors that influence the usage of TM Net Streamyx. These factors include the demographic factors such as gender, age, and education level, promotion factor, price factor, and the package of the product itself (Streamyx)'s factor. The targeted respondents will be 100 people of the TM Net Streamyx customers at the residents of section 11 Shah Alam. In order to gain the relevant data for the purpose of this study, the researcher has decided to get the information from the secondary data as well as primary data. For primary data, the researcher conducts a survey, through personal interview and self-administered questionnaires. For secondary data, the researcher includes the TM Net articles, user's manual, newspaper, internet, journal, and others. The data that had been collected was analyzed by using Statistical Package for the Social Science (SPSS) programme. The answers that are related to the objectives were also determined by examining the frequency distribution and cross tabulation. From the findings, the researcher can conclude that most of the residents at Section 11 Shah Alam are switching from the Dial-up Internet access to TM Net Streamyx and the main reason for switching from the Dial-up Internet access to TM Net Streamyx is because of the speed. This is because, the speed of TM Net Streamyx is high which is from 512k up to 2mbps compared to the Dial-up Internet access with only 56.6kbps. Apart from that, most of the TM Net Streamyx users use TM Net Streamyx or surf the Internet 16 to 20 times per week and between 2 to 5 hours for each usage. It shows that they are the high intense user of TM Net Streamyx. In terms of demographic data, most of the TM Net Streamyx users are male aged between 21 to 30 years old. For the education level, majority of them are degree holders. Besides that, most of the customers agree that the promotion done by TM Net is attractive and they can see the advertisement of TM Net Streamyx everywhere. In terms of price, the cost is reasonable and cheaper compared to the Dial-up Internet access. Apart from that, the TM Net Streamyx users are satisfied with the features and the packages of TM Net Streamyx and agree that the package of the product itself (Streamyx) is the biggest factor which makes them use TM Net Streamyx.